Inovasi Administrasi Pendidikan Pada Era Digital - Sri Putri Mayanti; ArisMunandar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of digital technology has transformed many aspects of everyday life, including the field of educational management. Previously, educational administration processes were carried out manually, but they have now shifted to digital systems that are more efficient, transparent, and accountable. This article explains various forms of innovation in educational administration in the digital era, the benefits gained, and the challenges that arise during their implementation. This study employs a literature review approach by analyzing various sources and previous research related to digital educational management. The results show that innovations such as education information systems, administrative services through applications, and the use of cloud computing and big data technologies can improve the effectiveness of managing educational institutions. However, several obstacles still persist, including inadequate infrastructure, low digital literacy among educational staff, and data security issues. Therefore, developmental strategies focused on enhancing the competencies of educational personnel, improving facilities, and strengthening government policy support are needed. In this way, innovation in digital educational management can provide real benefits for improving the quality of educational services sustainably.